Mathematical Structure Analysis of Game Problems - Dawood, Haithm Saleem (Al-Nahrain Journal of Science, 2011)
In this paper, we are present a novel direction to identify efficient and inefficient strategies of the game problems, based on the features of system of linear inequalities. Definitions and simple illustrated example have been presented.